DEVELOPING PRIMARY SCHOOL STUDENTS' SPEAKING SKILLS THROUGH FOLKLORE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article describes the theoretical basis and importance of the formation of speech skills in elementary school students through the works of folk oral works given in the elementary school textbook.